FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS AUDIT KAP DI JAWA TENGAH (Students' Journal of Accounting and Banking, 2013)
The purpose of this research is to know and make sure how big are the effects of independency, experience, due professional care, and accountability, on audit quality. The population of this research are auditors that are working at CPA Firms in Central Java Province. Sampling is done by using convenience sampling method, and the amount of the respondents for samples are 47. Data are obtained through primary data by using questionnaires. The questionnaires that are distributed to the CPA Firms located in Central Java Province, consisted of the indicators of the variables that used in this research. Data analysis technique that used in this research is multiple linear regression analysis.The result of hypothesis test of this research showed that experience gives positive and insignificant effects on audit quality, while due professional care gives negative and insignificant effects on audit quality. On the other hand, independency and accountability gives positive and significant effects on audit quality. Simultaneously, all of the independent variables gave positive and significant effects on audit quality, with the level of effects was 47,4%. The researcher suggested for the future research to add the variables, especially the independent variables, and to increase the scope of research.Keywords: independency, experience, due professional care, accountability, and audit quality